Photoactivatable RuII Complex Bearing 2, 9‐Diphenyl‐1, 10‐phenanthroline: Unusual Photochemistry and Significant Potency on Cisplatin‐Resistant Cell Lines. Issue 22 (29th May 2018) - Mansour, Najwa; Mehanna, Stephanie; Mroueh, Mohamad A.; Audi, Hassib; Bodman‐Smith, Kikki; Daher, Costantine F.; Taleb, Robin I.; El‐Sibai, Mirvat; Khnayzer, Rony S.
Abstract : The current study investigates [Ru(bipy)2 (dpphen)]Cl2 [where bipy = 2, 2′‐bipyridine and dpphen = 2, 9‐diphenyl‐1, 10‐phenanthroline] (complex1 ) for photoactivatable chemotherapy (PACT) application on five cancer cell lines. [Ru(bipy)2 (phen)]Cl2 [where phen = 1, 10‐phenanthroline] (complex2 ) was included as an unstrained control. Upon excitation with visible light, complex2 proved to be photostable while complex1 underwent a quantitative dissociation of the bipy ligand and formation of a Ru II polypyridyl aqua complex in water. Complex1 demonstrated only marginal activity in the dark; its cytotoxicity increased significantly upon photoactivation with a high phototoxicity index (PI = [IC50 dark]/[IC50 light]) ranging from 39.2‐fold in A549 to over 100‐fold in MDA‐MB‐231. Complex2, on the other hand, did not show much difference in anticancer activity between dark and light conditions. Importantly, the IC50 of the photoproduct of complex1 was several folds lower than that of cisplatin in all tested cell lines. Furthermore, the dissociating ligand (bipy) was biologically inert in almost all cell lines investigated confirming that phototoxicity was mediated primarily by the Ru aqua complex that is released upon irradiation. In conclusion, the Ru‐centered complex1 could represent a potential photoactivatable chemotherapeutic drug that increases selectivity to tumors and offers alternative treatment in the light of increasing cisplatin resistance. Abstract : [Ru(bipy)2 (dpphen)]Cl2 [where bipy = 2, 2′‐bipyridine and dpphen = 2, 9‐diphenyl‐1, 10‐phenanthroline] (complex1 ) exhibited up to100‐fold increase in cytotoxicity upon irradiation when tested on five cancer cell lines including cisplatin‐resistant ones. The ejected bipy ligand displayed minimal potency and therefore phototoxicity was attributed to the formation of the Ru‐aqua complex.